Temple Bar An Egyptian Novel. - Abdelmegid, Bahaa (The American University in Cairo Press, 2014)
Dublin is alien territory for young and impoverished Egyptian academic Mutazz. Mutazz has enough problems with his family's high expectations and the unrequited, idealized love that he left behind in Cairo. Now he has to deal with cantankerous landlords, the inscrutable local women, the Irish judiciary, haunted seminaries, and cold winter nights selling flowers on the banks of the Liffey to make ends meet. His own personal demons travel with him, especially the clash between his sexual desires and his reluctance to become emotionally entangled with anyone other than his version of the ideal wo.